2021
DOI: 10.1371/journal.pone.0254360
|View full text |Cite
|
Sign up to set email alerts
|

Human mobility in a Bronze Age Vatya ‘urnfield’ and the life history of a high-status woman

Abstract: In this study, we present osteological and strontium isotope data of 29 individuals (26 cremations and 3 inhumations) from Szigetszentmiklós-Ürgehegy, one of the largest Middle Bronze Age cemeteries in Hungary. The site is located in the northern part of the Csepel Island (a few kilometres south of Budapest) and was in use between c. 2150 and 1500 BC, a period that saw the rise, the apogee, and, ultimately, the collapse of the Vatya culture in the plains of Central Hungary. The main aim of our study was to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 93 publications
(118 reference statements)
1
12
0
Order By: Relevance
“…Cranial bones represent on average about 15% of the total weight of a human skeleton–calculated as a mean value across different developmental stages [ 64 – 67 ]. Furthermore, published studies on the ratio between weights of cranial and post-cranial fragments in protohistoric funerary contexts show a relative selective representation of the cranial skeleton [ 22 , 37 ], suggesting an intentional and preferential selection of the head/face remains of the deceased for the burial. Both the identification of a preferential spot and orientation of the body on the pyre, along with expected representations of the cranial and post-cranial skeletons in the cremation site of Salorno would both support hypothesis A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cranial bones represent on average about 15% of the total weight of a human skeleton–calculated as a mean value across different developmental stages [ 64 – 67 ]. Furthermore, published studies on the ratio between weights of cranial and post-cranial fragments in protohistoric funerary contexts show a relative selective representation of the cranial skeleton [ 22 , 37 ], suggesting an intentional and preferential selection of the head/face remains of the deceased for the burial. Both the identification of a preferential spot and orientation of the body on the pyre, along with expected representations of the cranial and post-cranial skeletons in the cremation site of Salorno would both support hypothesis A.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these operations must have entailed a symbolic/religious value, confirmed by the continuity of this ritual over many centuries across the late 2 nd and 1 st millennium BCE in Northern Italy. In fact, the transition from inhumation to the widespread cremation ritual in various European regions during the central and later phases of the Bronze Age has been interpreted as a moment of shift in the phenomenology or the aesthetics of death, of the memory of the ancestors, and of the relationship with the world and matter [ 15 , 16 , 19 – 21 ]–possibly sided by ecological, social, political, as well as sanitary reasons [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radiocarbon dates are available for Hungary (Dani et al, 2016;Kiss et al, 2019;Major et al, 2019;Cavazzuti et al, 2021); northeastern Serbia (Gavranović & Kapuran, 2021;Kapuran et al, 2020;Mehofer et al, 2021); and the Terramare area (Cardarelli, 2014). There are, however, three main issues that affect attempts to build an absolute chronological framework when dealing with this kind of context.…”
Section: Conclusion: Homophily Mobility Geopolitics and Different Att...mentioning
confidence: 99%
“…Women, and especially high-status women, seem to have had an especially important role in the selective diffusion of ideas and beliefs, as their high degree of mobility in this phase has been demonstrated by several isotope studies (Cavazzuti et al, 2019a(Cavazzuti et al, , 2021Frei et al, 2015Frei et al, , 2017Knipper et al, 2017). Female mobility is normally associated with exogamy and patrilocality, but other options, in which women exercise agency rather than being subjected to it, should not be dismissed.…”
Section: Conclusion: Homophily Mobility Geopolitics and Different Att...mentioning
confidence: 99%
“…A complex territorial organization also characterizes BA through the development of hierarchical residential systems, which again suggest a complex social organization: nucleated settlements, fortified villages, pile-dwellings, and terramare hosted a growing number of inhabitants (Bettelli 2006; Fokkens, Harding 2013). Despite the increasing establishment of settlements, the discovery of exotic items and recent stable isotope analysis on human bones suggest a rise in both individual and artifact mobility in the BA (e.g., Knipper et al 2017; Cavazzuti et al 2019; Cavazzuti et al 2021). Goods and people were involved in complex exchange networks (Blake 2014; Cavazzuti et al 2019), whose effects could be identified in heterogeneous lifestyles and bio-cultural characteristics (Fokkens, Harding 2013; Bietti Sestieri 2015).…”
Section: Introductionmentioning
confidence: 99%